2016
DOI: 10.1016/j.gr.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Rifting, subduction and collisional records from pluton petrogenesis and geochronology in the Hindu Kush, NW Pakistan

Abstract: New U-(Th)/Pb geochronology and geochemical analyses of plutonic bodies in the Hindu Kush range, NW Pakistan, provide insight on the crustal growth and tectonic evolution of the southern Eurasian margin. These new data outline a protracted magmatic history that spans the Cambrian to the Neogene (ca. 538 to 23 Ma) and record a variety of petrogenetic associations variably influenced by within plate, volcanic arc, and collision tectonic environments. The Kafiristan pluton (538 ± 4 to 487 ± 3 Ma) yields geochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 79 publications
(162 reference statements)
0
24
0
Order By: Relevance
“…Guillot et al., ; Rutte, Ratschbacher, Khan, et al., ) or to the Tethyan Himalaya–Lhasa microcontinent collision and subsequent oceanic slab flattening (Van Hinsbergen et al., ). Peak metamorphism is reached at 580–600°C and ˜0.6 GPa for the staurolite schist, and 700–750°C and 0.7–0.8 GPa for the sillimanite migmatites. Late Oligocene (28–23 Ma) crustal anatexis, which culminated in the intrusion of the Garam Chasma leucogranite (27–23 Ma; for example, Faisal et al., ). Rocks in the Chitral area underwent near‐isothermal decompression/exhumation (over 0.1 GPa; 3–7 km).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Guillot et al., ; Rutte, Ratschbacher, Khan, et al., ) or to the Tethyan Himalaya–Lhasa microcontinent collision and subsequent oceanic slab flattening (Van Hinsbergen et al., ). Peak metamorphism is reached at 580–600°C and ˜0.6 GPa for the staurolite schist, and 700–750°C and 0.7–0.8 GPa for the sillimanite migmatites. Late Oligocene (28–23 Ma) crustal anatexis, which culminated in the intrusion of the Garam Chasma leucogranite (27–23 Ma; for example, Faisal et al., ). Rocks in the Chitral area underwent near‐isothermal decompression/exhumation (over 0.1 GPa; 3–7 km).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, based on geochemical data, it has been demonstrated that the Cretaceous magmatic intrusions represent the development of an Andean‐style arc along the southern Eurasian margin due to the northward subduction of the Neotethys ocean (Figure b; for example, Chapman, Scoggin, et al., ; Faisal et al., ; Kapp, DeCelles, Gehrels, Heizler, & Ding, ; Robinson, ; Schwab et al., ). This magmatism occurred from 130 to 95 Ma in the Karakoram (Aminov et al., ; Debon, Le Fort, Dautel, Sonet, & Zimmermann, ; Fraser et al., ; Heuberger et al., ; Robinson, ), and to 105 Ma in the North Lhasa (Tibet; Chen et al., ; Sui et al., ; Zhu et al., ), with a high‐flux event between 110 and 105 Ma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations